The resurrection fo the chinese church - Lambert, Tony (Wheaton Harold Shaw Publishers, 1994)
Originally presented as the author's thesis (Master of Philosophy)--Oxford Polytechnic, 1989-1990. Includes bibliographical references (p. [326]-342) and index.
Keywords: Christianity -- China. China -- Church history -- 20th century. Christianity. China. Christianity -- History China